Emotional Intelligence and Investment Decision of Investors in Nepalese Stock Market - Adhikari, Hari Prasad; Shahu , Dil Krishna (Journal of Nepalese Management Academia, 2024)
The primary of objective of this study is to investigate the relationship between emotional intelligence and investment decision. The present study employed survey research methodology using primary data collected using structured questionnaires from 172 respondents of investors in stock market from Kathmandu valley of Nepal. The linear relationship between the emotional intelligence dimensions and investment decision was examined using multiple linear regression was used. The emotional intelligence dimensions considered for the study were self-awareness, self-management, social awareness and relationship management. The study provided empirical evidence that all the dimensions of emotional intelligence i.e. self-awareness, social awareness, and relationship management except self-management have a significant positive effect on the investment decision of investors in Nepal. This study suggested that investors should focus on improving their emotional intelligence, particularly self-awareness, social awareness, and relationship management to achieve success in investment decision.